EXCAVATION OF THE FOUNDATION OF PIERS S1L AND S1R OF THE VRANDUK I BRIDGE BY CONTROLLED BLASTING ON THE MOTORWAY ROUTE: ZENICA MUNICIPALITY NORTHERN ADMINISTRATIVE BOUNDARY - ZENICA NORTH - Ekrem Bektašević; Reuf Kadrić; Marin Nikolić; Kemal Gutić; Sead Kadrić (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2023)
The Vranduk I bridge is located on the motorway route, on the part of the subsection: Zenica Municipality Northern Administrative Boundary - Zenica North. The bridge consists of two parallel structures, one for the left side, and the other for the right side of the motorway. The Vranduk I bridge rests on three piers. The paper deals with the excavation of the pier site S1R and S1L by controlled blasting. By correctly choosing the equipment for drilling blast holes, defining the drilling and blasting parameters and excavation steps, a minimal zone of damage to the surrounding rock outside the line of excavation of pier sites S1R and S1L, which is inevitable during blasting excavation, has been achieved, which has the effect of preserving the bearing capacity of the rock mass as the most important supporting element.